Burnout syndrome in teachers from Latin America: A systematic review - Tabares-Díaz, Yuranny Alejandra; Martínez-Daza, Viviana Alexandra; Matabanchoy-Tulcán, Sonia Maritza (Universidad y Salud, 2020)
Introduction: The Burnout Syndrome (BS) is understood as a phenomenon that includes emotional fatigue, depersonalization, and reduced personal accomplishment, which have multivariate consequences at physical, psychological, social, and occupational levels. Objective: To examine Latin American reports on BS in teachers that were published between 2008 and 2018. Materials and methods: A systematic literature search was conducted, which was based on the PRISMA-P guidelines and included the Web of Science, Scopus, Directory of Open Access Journals and EBSCOhost databases. The keywords used were: “Burnout” AND “teachers”, together with the corresponding translation in English. Results: A total of 53 articles were selected, which were mostly published in Brazil in 2014, 2017, and 2018. The majority of reports were on teachers from basic education institutions and corresponded to quantitative studies focused on the analysis of variables related to BS. Conclusions: Latin American research on BS is mostly concentrated in some Latin American countries and has specific paradigmatic and methodological scopes. The need to carry out primary studies about this phenomenon is highlighted.